MENGKOMSUMSI MIRAS DAN PERILAKU REMAJA DI NEGERI LAYENI KECAMATAN TNS KABUPATEN MALUKU TENGAH - Hobarth Williams Soselisa (BADATI, 2022)
ABSTRACTThat excessive alcohol consumption among teenagers can affect health, cannot continue education in stages and on the other hand deviant behavior is unavoidable. This also affects the good name of the family.The purpose of this study was to determine the extent to which alcohol consumption behavior and its impact on adolescent behavior and the role of the government and society of Layeni Negeri in dealing with this problem.This type of research is quantitative which produces descriptive data. Data collection methods are Questionnaire or a list of questions, interviews, non-involved observations and literature related to alcohol consumption and its impact on adolescent behavior.The results of the study prove that the availability of sopi in Layeni is sufficient so that it has a negative impact on the behavior of teenagers who consume it and is full of uncontrollable crimes such as theft, fights and violence to others. The results of the study show that the health conditions of adolescents who consume alcohol also have an effect and from a physical point of view they also experience problems as well as some who cannot continue their education in stages.